Preparation method of graphene reinforced low-melting-point metal phase change composite material

Through the air pressure impregnation process of graphene aerogel and low-melting metal, a honeycomb pore structure is formed, which solves the problem of leakage of liquid metals easily and achieves graphene enhanced low-melting metal phase change with high thermal conductivity and high energy storage density Composite materials suitable for thermal management and heat storage materials.

CN119286475AActive Publication Date: 2025-01-10UNIV OF SCI & TECH BEIJING
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411242988.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-10
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The existing low-melting point phase-changing metal is prone to leakage in liquid state, resulting in the risk of corrosion and electrical short circuit. The existing packaging process cannot effectively improve its thermal conductivity and energy storage density, limiting its in thermal management materials and heat storage materials. Application.

Method used

Graphene aerogel is used as the reinforcement, and the low-melting metal is penetrated into the honeycomb pores through the pneumatic impregnation process to form a graphene/metal composite material, and the high thermal conductivity and pore structure of graphene are used to limit the flow and leakage of metals. Improve the reliability and performance of composite materials.

Benefits of technology

It achieves high reliability, excellent thermal and electrical conductivity, and has a wide range of application. It can regulate the mechanical and thermal conductivity of composite materials, significantly improves thermal conductivity and energy storage density, and avoids interface introduction and performance losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286475A_ABST
    Figure CN119286475A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of phase change materials. The preparation method of the graphene reinforced low-melting-point metal phase change composite material comprises the following steps that (1) honeycomb-shaped graphene aerogel is prepared; (2) cutting the graphene aerogel into a required shape, putting the graphene aerogel into a customized graphite pattern mold, putting the filled pattern mold into a graphite sleeve, and putting a low-melting-point metal block on the upper part of the pattern mold to prepare a complete mold; 3) placing the mold prepared in the step 2) in an induction heating area of an air pressure infiltration furnace, vacuumizing the furnace body, heating the mold under a vacuum condition, and preserving heat; (4) injecting high-purity argon to pressurize and inflate the furnace; and (5) heating is stopped, the mold is taken out after furnace cooling is conducted to the room temperature, demolding is conducted, and the graphene reinforced low-melting-point metal phase change composite material is obtained. According to the method, high reliability, high heat conductivity and high energy storage density of the low-melting-point metal phase change material are achieved, and the method has wide application prospects in the fields of heat management and energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of phase change materials, and in particular relates to a method for preparing a graphene-enhanced low-melting-point metal phase change composite material. Background Art

[0002] Solid-liquid phase change materials can realize large-scale absorption or release of energy through the transformation of the solid-liquid state of the material, and have important application prospects in the fields of electronic device thermal management, solar energy utilization, waste heat recovery, etc. Solid-liquid phase change materials can be divided into organic phase change materials and inorganic phase change materials. Among them, organic phase change materials mainly include organic substances such as hydrocarbons and alcohols. They have low density and large phase change enthalpy per unit mass, but their low intrinsic thermal conductivity (0.1-0.2W / mK) limits their application. Low-melting-point phase change metals in inorganic phase change materials refer to metals such as gallium, indium, bismuth, tin, and alloys with melting points below 300°C composed of different proportions of metals and elements such as lead, cadmium, and zinc. They have high thermal conductivity (10-61W / mK) and high energy storage density. They are ideal passive thermal management materials, thermal interface materials, and phase change energy storage materials.

[0003] However, low-melting-point phase change metals have good fluidity in the liquid phase and are prone to leakage, resulting in metal corrosion and electrical short circuits. They cannot be used alone as thermal management materials and heat storage materials. There are currently two main ideas to solve the leakage problem: one is to use encapsulation technology to encapsulate low-melting-point phase change metal particles in an outer shell to form phase change microcapsules, and then use the microcapsules as fillers and mix them with an organic matrix to form a composite material. However, this process requires heating and melting the metal in water or an organic solvent, so it is only suitable for metals with lower melting points. In addition, this method will introduce additional interfaces while solving the liquid metal leakage problem, and the proportion of microcapsules added to the composite material is limited, resulting in low thermal conductivity and energy storage density of the composite material. The thermal conductivity is only 0.45~3.23W / mK, and the energy storage density is only 71.73~126.72J / cm 3 , such as Deng C, Zhang X, Peng J, et al. 51 Bi 32.5 Sn 16.5@SiO2 microcapsules-based composite phase change materials with high thermal conductivity and heat storage density for electronics thermal management[J].Journal of Energy Storage,2024,86:111432 and the literature Wang S,Zhao X,Wang Z,et al.Micro-encapsulation of a low-melting-point alloy phase change material and its application in electronicthermal management[J].Journal of Cleaner Production,2023,417:138058 mentioned; the second is to composite the porous material with the low melting point metal through the vacuum infiltration process, and use the capillary force of the pores to limit the flow of the liquid metal after the phase change, providing it with shaping ability. The porous materials currently used include metal foams and flexible organic foams, but metal foams will react with liquid metals to form intermetallic compounds, and flexible organic foams have low thermal conductivity and are easy to deform, so the performance of phase change composite materials prepared by the two foams has a lot of room for improvement. Therefore, it is urgent to find new processes to obtain low-melting-point metal-based phase change composite materials with high reliability, high thermal conductivity and high energy storage density. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a graphene-enhanced low-melting-point metal phase change composite material. A rigid graphene aerogel with through honeycomb pores is used as a reinforcing phase, and a graphene / metal composite material is prepared by a gas pressure infiltration process to obtain a graphene-enhanced low-melting-point metal phase change composite material with high reliability, high thermal conductivity and high energy storage density.

[0005] The technical solution of the present invention is:

[0006] A method for preparing a graphene-enhanced low-melting-point metal phase-change composite material comprises the following steps:

[0007] 1) adding graphene powder and dispersant to deionized water, mixing evenly and dispersing by ultrasonic, then adding sodium alginate to completely dissolve it, and obtaining a sodium alginate sol in which graphene powder is stably dispersed; transferring the sol to a mold, spraying a gelling agent evenly on the upper surface of the sol, standing to wait for gelation to be completed, and obtaining a hydrogel after demolding; freeze-drying the hydrogel to remove water, and then removing organic matter by high-temperature debinding to obtain a honeycomb graphene aerogel;

[0008] 2) cutting the graphene aerogel into a desired shape and placing it in a customized graphite mold, placing the filled mold in a graphite sleeve and placing a low melting point metal block on the upper part of the mold to make a complete mold;

[0009] 3) placing the mold obtained in step 2) in the induction heating area of ​​the air pressure infiltration furnace, evacuating the furnace body, and heating and keeping the mold warm under vacuum conditions;

[0010] 4) Injecting high-purity argon gas to pressurize and inflate the furnace, so that the liquid metal penetrates into the pores of the graphene aerogel in the mold under the action of the high-pressure gas;

[0011] 5) Stop heating, cool to room temperature in the furnace, take out the mold and demould, and obtain the graphene-enhanced low-melting-point metal phase change composite material.

[0012] Furthermore, in step 1), the mass of the graphene powder is 0.5-3% of the mass of water, and the concentration of sodium alginate is 0.5-2%.

[0013] Furthermore, the dispersant in step 1) is one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol and polyethylene oxide-polypropylene oxide copolymer, and the mass of the dispersant is 5-10% of the mass of the graphene powder.

[0014] Furthermore, the gelling agent in step 1) is one or more of calcium chloride, cupric chloride, copper sulfate, nickel chloride, nickel nitrate, cobalt chloride or ferrous chloride solution, the solution concentration is 1 to 4 mol / L, and the gelling reaction time is 4 to 10 hours.

[0015] Furthermore, the freeze drying in step 1) is to freeze dry the hydrogel at -60°C and 1 Pa for 30 h to 72 h, preferably 36 h to 48 h.

[0016] Furthermore, step 1) performs high-temperature debinding in a tubular furnace or a vacuum heat treatment furnace, the debinding atmosphere is an inert gas or a vacuum environment, the debinding temperature is 600-650° C., and the debinding time is 3-5 hours.

[0017] Furthermore, the graphene aerogel used in step 2) is composed of oriented graphene nanosheets and highly interconnected honeycomb pores, with a pore size of 20 to 200 μm, a graphene volume fraction of 2 to 10%, and a porosity of 90 to 98%.

[0018] Further, the low melting point metal used in step 2) includes one or more of gallium, indium, bismuth, tin, gallium-aluminum alloy, gallium-indium alloy, gallium-bismuth alloy, gallium-tin alloy, gallium-indium-tin alloy, indium-bismuth alloy, indium-tin alloy, indium-cadmium alloy, indium-bismuth-tin alloy, indium-bismuth-cadmium alloy, bismuth-tin alloy, bismuth-cadmium alloy, bismuth-tin-cadmium alloy, bismuth-lead-cadmium alloy, bismuth-tin-lead alloy, bismuth-tin-zinc alloy, tin-lead alloy, tin-zinc alloy, tin-cadmium-lead alloy, indium-bismuth-tin-lead alloy, bismuth-tin-lead-cadmium alloy, and lead-antimony alloy.

[0019] Furthermore, in step 3), the vacuum degree is lower than 0.1Pa.

[0020] Furthermore, in step 3), the heating temperature of the mold is 100-350° C., and the insulation time is 5-30 min.

[0021] Furthermore, in step 4), the gas pressure in the furnace is 0.5-2.0 MPa.

[0022] The invention relates to a graphene-enhanced low-melting-point metal phase-change composite material obtained by the preparation method, wherein the volume fraction of graphene in the graphene-enhanced low-melting-point metal phase-change composite material is 2-10%.

[0023] Compared with other technologies, the outstanding advantages of the present invention are:

[0024] The graphene-enhanced low-melting-point metal phase-change composite material prepared by the present invention has high reliability, and the micron-scale pores of the graphene aerogel limit the leakage of liquid metal through capillary force; in addition, the bionic honeycomb graphene aerogel has high compressive strength and compression modulus, so that the composite material also has a certain ability to resist compression deformation after the metal is melted, thereby further improving the reliability of the composite material.

[0025] The graphene-enhanced low-melting-point metal phase-change composite material prepared by the present invention has excellent thermal and electrical conductivity. The graphene aerogel and the low-melting-point metal constitute a dual-continuous thermal and electrical conductivity path, eliminating the adverse effect of the interface on carrier scattering; in addition, the directionally arranged graphene nanosheets can further improve the out-of-plane thermal and electrical conductivity of the composite material.

[0026] The graphene-enhanced low-melting-point metal phase-change composite material prepared by the present invention has a high energy storage density. The porosity of the graphene aerogel used is 90-98%, and the pores are all through holes. Combined with the air pressure infiltration process, the phase-change metal can be densely filled inside the aerogel, ensuring that the phase-change metal has a volume fraction as high as possible, thereby reducing the loss of the composite material's energy storage density.

[0027] Compared with the microencapsulation process, the process used in the present invention has the following advantages: a wide range of applications, and composite materials can be prepared using low-melting-point metals of any composition; product performance is adjustable, and the mechanical properties, thermal conductivity and phase change properties of the composite materials can be regulated by changing the volume fraction of graphene to meet the needs of different scenarios; there is no need to introduce additional interfaces and organic matter, and the thermal conductivity and energy storage density are high.

[0028] Compared with the existing porous material packaging process, the present invention uses honeycomb graphene aerogel as packaging material, which has the following advantages:

[0029] Compared with the metal foam encapsulation process, graphene aerogel has small pore size, strong capillary force and low liquid metal leakage rate; graphene does not react with liquid metal, and the long-term stability of the composite material's performance is better.

[0030] Compared with the flexible organic foam packaging process, the rigid graphene aerogel has higher specific strength and specific modulus, is not easy to deform, and the composite material is more reliable after the metal is melted; the thermal conductivity and electrical conductivity of graphene aerogel are much higher than those of organic foam, and the composite material has better thermal and electrical conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings used in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 This is a scanning electron microscope surface image of the graphene aerogel prepared in Example 1 of the present invention;

[0033] Figure 2 This is a scanning electron microscope cross-sectional view of the graphene aerogel prepared in Example 1 of the present invention;

[0034] Figure 3 This is a scanning electron microscope surface image of the graphene aerogel / Wood's alloy composite material prepared in Example 1 of the present invention;

[0035] Figure 4 This is a scanning electron microscope cross-sectional view of the graphene aerogel / Wood's alloy composite material prepared in Example 1 of the present invention;

[0036] Figure 5 This is a comparison diagram of the macroscopic morphologies of the graphene aerogel / Wood's alloy composite material and Wood's alloy prepared in Example 1 of the present invention before phase transition at 25°C (A) and after phase transition at 100°C (B). DETAILED DESCRIPTION

[0037] The specific implementation methods of the present application are described in detail below with reference to the accompanying drawings. It should be noted that the technical features or combinations of technical features described in the following embodiments should not be considered isolated, and they can be combined with each other to achieve better technical effects.

[0038] The present invention relates to a method for preparing a graphene-enhanced low-melting-point metal phase-change composite material, wherein a rigid graphene aerogel having through honeycomb pores is used as a reinforcement, and the graphene-enhanced low-melting-point metal phase-change composite material is prepared by a gas pressure infiltration method, comprising the following steps:

[0039] 1) adding graphene powder and dispersant into deionized water, stirring them evenly by magnetic stirring, and then dispersing them ultrasonically under ice bath conditions, then adding sodium alginate, and completely dissolving the sodium alginate by magnetic stirring at room temperature to obtain a sodium alginate sol in which graphene powder is stably dispersed; transferring the sol into a mold, spraying a gelling agent evenly on the upper surface of the sol, standing the sol to wait for gelation to be completed, and obtaining a hydrogel after demolding; freeze-drying the hydrogel to remove water, and then removing organic matter by high-temperature debinding to obtain a honeycomb graphene aerogel with good pore permeability and excellent compressive performance;

[0040] 2) cutting the graphene aerogel into the desired shape and placing it in a customized graphite mold, placing the filled mold in a graphite sleeve and placing a low melting point metal block on the top of the mold to make a complete mold;

[0041] 3) placing the obtained mold in the induction heating area of ​​the air pressure impregnation furnace, evacuating the furnace body, and heating and keeping the mold obtained in step 2) under vacuum conditions;

[0042] 4) Injecting high-purity argon gas to pressurize and inflate the furnace, so that the liquid metal penetrates into the pores of the graphene aerogel in the mold under the action of the high-pressure gas;

[0043] 5) Stop heating, cool to room temperature in the furnace, take out the mold and demould, and obtain the graphene-enhanced low-melting-point metal phase change composite material.

[0044] In this process, debinding refers to keeping the material warm for a period of time under certain temperature and atmosphere conditions to volatilize and discharge organic matter (the organic matter here refers to alginate, polyvinyl pyrrolidone, etc.).

[0045] The low melting point metal used in step 2) includes one or more of gallium, indium, bismuth, tin, gallium-aluminum alloy, gallium-indium alloy, gallium-bismuth alloy, gallium-tin alloy, gallium-indium-tin alloy, indium-bismuth alloy, indium-tin alloy, indium-cadmium alloy, indium-bismuth-tin alloy, indium-bismuth-cadmium alloy, bismuth-tin alloy, bismuth-cadmium alloy, bismuth-tin-cadmium alloy, bismuth-lead-cadmium alloy, bismuth-tin-lead alloy, bismuth-tin-zinc alloy, tin-lead alloy, tin-zinc alloy, tin-cadmium-lead alloy, indium-bismuth-tin-lead alloy, bismuth-tin-lead-cadmium alloy, and lead-antimony alloy.

[0046] Example 1

[0047] To prepare graphene aerogel, first disperse 0.2g of graphene powder and 0.02g of polyvinyl pyrrolidone in 20mL of deionized water by magnetic stirring, and then ultrasonically disperse in an ice bath for 3h to further improve the dispersibility of graphene. Add 0.1g of sodium alginate to the dispersion and stir magnetically for 2h to completely dissolve the sodium alginate. Transfer the sol to a mold, spray 10mL of 2mol / L calcium chloride solution on the upper surface of the sol, let it stand for 6h, and demold after the sol gelation is completed to obtain a hydrogel. Freeze-dry the hydrogel at -60℃ and 1Pa for 36h, and then debind at 620℃ under argon protection for 3h to obtain a rigid graphene aerogel with through honeycomb pores. The microscopic morphology of the sample was characterized by scanning electron microscopy, and its surface image and cross-sectional image are shown as follows: Figure 1 and Figure 2 As shown, the prepared graphene aerogel has hexagonal honeycomb pores, and the pores have good vertical connectivity.

[0048] The graphene aerogel is cut and loaded into the mold, and then the loaded mold is placed in the graphite sleeve, and the melting point of 70°C and the composition of Bi 50 Pb 26.7 Sn 13.3 Cd 10 , a Wood's alloy block with a thermal conductivity of 20.3W / mK is placed on the top of the mold, and the entire filled mold is placed in the induction heating zone of the air pressure impregnation furnace, and the vacuum system and the pressurized gas system are connected. Turn on the vacuum system and evacuate the furnace until the vacuum degree is less than 0.1Pa. Turn on the circulating water, start the induction heater, heat the mold to 130°C and keep it warm for 30 minutes. Turn on the pressurized gas system to inject high-purity argon into the furnace. When the gas pressure in the furnace reaches 1.0MPa, turn off the pressurized gas system. Stop heating, turn off the circulating water when the furnace temperature drops to room temperature, take out the mold and demold it to obtain a circular flake-shaped graphene aerogel / Wood's alloy composite product with a diameter of 20mm and a thickness of 4mm. The micromorphology of the sample was characterized by a scanning electron microscope, and its surface image and cross-sectional image are shown as follows. Figure 3 and Figure 4As shown, the honeycomb skeleton structure of the graphene aerogel in the composite material is intact, the alloy phase is densely filled inside the aerogel, and the interface between the two is well bonded. The thermal conductivity of the prepared graphene aerogel / Wood's alloy composite material is 33.5W / mK, the graphene volume fraction is 4.0%, and the density is 9.2g / cm 3 , the energy storage density is 374.6J / cm 3 .

[0049] Figure 5 The macroscopic morphologies of the prepared graphene aerogel / Wood's alloy composite material and Wood's alloy at 25°C and 100°C are compared. It can be seen that at 100°C, the appearance of Wood's alloy changes significantly due to the melting of the alloy, while the appearance of the composite material does not change significantly at 100°C, indicating that graphene aerogel can provide excellent shaping effects for low-melting-point metals at temperatures above their melting points.

[0050] Example 2

[0051] To prepare graphene aerogel, first disperse 0.6g of graphene powder and 0.06g of polyethylene glycol in 30mL of deionized water by magnetic stirring, and then ultrasonically disperse for 3h in an ice bath to further improve the dispersibility of graphene. Add 0.3g of sodium alginate to the dispersion and stir magnetically for 3h to completely dissolve the sodium alginate. Transfer the sol to a mold, spray 20mL of 3mol / L calcium chloride solution on the upper surface of the sol, let it stand for 5h, and demold after the sol gelation is completed to obtain a hydrogel. Freeze-dry the hydrogel at -60℃ and 1Pa for 48h, and then debind in a vacuum environment at 600℃ for 3h to obtain a rigid graphene aerogel with through honeycomb pores.

[0052] The graphene aerogel is cut and loaded into the mold, and then the loaded mold is placed in the graphite sleeve, and the melting point of 138°C and the composition of Bi 58 Sn 42, a bismuth-tin alloy block with a thermal conductivity of 18.7W / mK is placed on the top of the mold, and the entire filled mold is placed in the induction heating area of ​​the furnace, and the vacuum system and the pressurized gas system are connected. Turn on the vacuum system and evacuate the furnace until the vacuum degree is less than 0.1Pa. Turn on the circulating water, start the induction heater, heat the mold to 200℃ and keep it warm for 20min. Turn on the pressurized gas system to inject high-purity argon into the furnace. When the gas pressure in the furnace reaches 1.0MPa, turn off the pressurized gas system. Stop heating, turn off the circulating water when the furnace temperature drops to room temperature, take out the mold and demold, and obtain a circular sheet of graphene aerogel / bismuth-tin alloy composite material product with a diameter of 20mm and a thickness of 4mm. The honeycomb skeleton structure of the graphene aerogel in the composite material is intact, the alloy phase is densely filled inside the aerogel, and the interface between the two is well bonded. The thermal conductivity of the prepared graphene aerogel / bismuth-tin alloy composite material is 39.0 W / mK, the graphene volume fraction is 7.9%, and the density is 8.1 g / cm 3 , the energy storage density is 356.6J / cm 3 .

[0053] Example 3

[0054] To prepare graphene aerogel, first disperse 0.1g of graphene powder and 0.01g of polyvinyl alcohol in 20mL of deionized water by magnetic stirring, and then ultrasonically disperse for 3h under ice bath conditions to further improve the dispersibility of graphene. Add 0.1g of sodium alginate to the dispersion and stir magnetically for 2h to completely dissolve the sodium alginate. Transfer the sol to the mold, spray 5mL of 4mol / L calcium chloride solution on the upper surface of the sol, let it stand for 4h, and demold after the sol gelation is completed to obtain a hydrogel. Freeze-dry the hydrogel at -60℃ and 1Pa for 36h, and then debind at 640℃ under argon protection for 3h to obtain a rigid graphene aerogel with through honeycomb pores.

[0055] The graphene aerogel is cut and loaded into the mold, and then the loaded mold is placed in the graphite sleeve, and Sn with a melting point of 190°C and a composition of 86 Bi 14, a bismuth-tin alloy block with a thermal conductivity of 33.4W / mK is placed on the top of the mold, and the entire filled mold is placed in the induction heating area of ​​the furnace, and the vacuum system and the pressurized gas system are connected. Turn on the vacuum system and evacuate the furnace until the vacuum degree is less than 0.1Pa. Turn on the circulating water, start the induction heater, heat the mold to 250℃ and keep it warm for 25min. Turn on the pressurized gas system to inject high-purity argon into the furnace. When the gas pressure in the furnace reaches 1.2MPa, turn off the pressurized gas system. Stop heating, turn off the circulating water when the furnace temperature drops to room temperature, take out the mold and demold, and obtain a circular sheet of graphene aerogel / bismuth-tin alloy composite material product with a diameter of 20mm and a thickness of 4mm. The honeycomb skeleton structure of the graphene aerogel in the composite material is intact, the alloy phase is densely filled inside the aerogel, and the interface between the two is well bonded. The thermal conductivity of the prepared graphene aerogel / bismuth-tin alloy composite material is 38.5 W / mK, the graphene volume fraction is 2.1%, and the density is 7.5 g / cm 3 , the energy storage density is 276.1J / cm 3 .

[0056] Although several embodiments of the present invention have been given herein, those skilled in the art should understand that the embodiments of the present invention may be modified without departing from the spirit of the present invention. The above embodiments are merely exemplary and should not be used as a limitation on the scope of the present invention.

Claims

1. A method for preparing a graphene-enhanced low-melting-point metal phase change composite material, comprising the following steps: 1) adding graphene powder and dispersant to deionized water, mixing well and then dispersing by ultrasonic, then adding sodium alginate to completely dissolve it, and obtaining a sodium alginate sol in which graphene powder is stably dispersed; transferring the sol to a mold, spraying a gelling agent evenly on the upper surface of the sol, standing to wait for gelation to be completed, and obtaining a hydrogel after demolding; freeze-drying the hydrogel to remove water, and then removing organic matter by high-temperature debinding to obtain a honeycomb graphene aerogel; 2) cutting the graphene aerogel into a desired shape and placing it in a customized graphite mold, placing the filled mold in a graphite sleeve and placing a low melting point metal block on the upper part of the mold to make a complete mold; 3) placing the mold obtained in step 2) in the induction heating area of ​​the air pressure infiltration furnace, evacuating the furnace body, and heating and keeping the mold warm under vacuum conditions; 4) injecting high-purity argon gas to pressurize and inflate the furnace, so that the liquid metal penetrates into the pores of the graphene aerogel in the mold under the action of the high-pressure gas; 5) stopping heating, cooling the furnace to room temperature, taking out the mold and demoulding, thereby obtaining a graphene-enhanced low-melting-point metal phase change composite material.

2. The preparation method according to claim 1, wherein In step 1), the mass of the graphene powder is 0.5-3% of the mass of water, and the concentration of sodium alginate is 0.5-2%.

3. The preparation method according to claim 1, wherein In step 1), the dispersant is one or more of polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol and polyethylene oxide-polypropylene oxide copolymer, and the mass of the dispersant is 5-10% of the mass of the graphene powder.

4. The preparation method according to claim 1, wherein The gelling agent in step 1) is one or more of calcium chloride, cupric chloride, copper sulfate, nickel chloride, nickel nitrate, cobalt chloride or ferrous chloride solution, and the solution concentration is 1-4 mol / L. Preferably, the gelling reaction time is 4-10 hours.

5. The preparation method according to claim 1, wherein In step 1), high-temperature debinding is performed in a tubular furnace or a vacuum heat treatment furnace, the debinding atmosphere is an inert gas or a vacuum environment, the debinding temperature is 600-650° C., and the debinding time is 3-5 hours.

6. The preparation method according to claim 1, wherein The graphene aerogel used in step 2) is composed of oriented graphene nanosheets and highly interconnected honeycomb pores, with a pore size of 20 to 200 μm, a graphene volume fraction of 2 to 10%, and a porosity of 90 to 98%.

7. The preparation method according to claim 1, wherein The low melting point metal used in step 2) includes one or more of gallium, indium, bismuth, tin, gallium-aluminum alloy, gallium-indium alloy, gallium-bismuth alloy, gallium-tin alloy, gallium-indium-tin alloy, indium-bismuth alloy, indium-tin alloy, indium-cadmium alloy, indium-bismuth-tin alloy, indium-bismuth-cadmium alloy, bismuth-tin alloy, bismuth-cadmium alloy, bismuth-tin-cadmium alloy, bismuth-lead-cadmium alloy, bismuth-tin-lead alloy, bismuth-tin-zinc alloy, tin-lead alloy, tin-zinc alloy, tin-cadmium-lead alloy, indium-bismuth-tin-lead alloy, bismuth-tin-lead-cadmium alloy, and lead-antimony alloy.

8. The preparation method according to claim 1, wherein The vacuum degree in step 3) is lower than 0.1 Pa. Preferably, the heating temperature in step 3) is 100-350° C. and the insulation time is 5-30 min.

9. The preparation method according to claim 1, wherein The gas pressure in the furnace in step 4) is 0.5-2.0 MPa.

10. A graphene-enhanced low-melting-point metal phase-change composite material obtained by the preparation method according to any one of claims 1 to 9, wherein: The volume fraction of graphene in the graphene-enhanced low-melting-point metal phase-change composite material is 2-10%.

Citation Information

Patent Citations

  • Liquid metal aerogel as well as preparation method and application thereof

    CN111013503A

  • Low-melting-point metal shaped phase-change material and preparation method thereof

    CN111040736A

  • Coated phase change material as well as preparation method and application thereof

    CN117720887A

  • Aerogel-metal composite material, preparation method therefor and application thereof

    WO2017045273A1

  • Metal-graphene composite structure heat pipe and method for manufacturing same

    WO2023059124A1